A study on the public perception towards the impact of bureaucracy on government performance in 1 MOCC, MAMPU, Putrajaya / Nurul Atiqah Md Pilus - Md Pilus, Nurul Atiqah (2016)
A researcher had conduct a study on the public perception towards the impact of bureaucracy on government performance in 1 MOCC, Malaysian Administrative Modernization and Management Planning Unit (MAMPU), Putrajaya. In this study, there were 100 of civil servants in 1 MOCC, MAMPU, Putrajaya involved as the respondents. The study examines the correlation between impact of bureaucracy and perception of public servants at the area of study. There were four impacts of bureaucracy towards government performance that correlate with public perception which includes reputation of government, procedure, public officer and public trust. The results show that procedure has the high correlation on public perception towards the impact of bureaucracy.